Infection capability of SARS-CoV-2 on different surfaces. Issue 1 (1st January 2021) - Mohapatra, Ranjan K.; Das, Pradeep Kumar; Pintilie, Lucia; Dhama, Kuldeep
ABSTRACT: The novel Coronavirus Disease 2019 (COVID-19) has emerged as a global pandemic and has posed serious health hazards for the humanity since December 2019. Over 2.5 million deaths have been reported worldwide till date mainly due to rapid human-to-human transmission of this virus while affecting millions of people. The widespread propagation of this disease has radically changed the common practice of human's normal life. Numerous measures have been taken up by different health agencies and government bodies of several countries to combat the menace by attenuating the transmission of SARS-CoV-2. The emergence of a new UK variant B.1.1.7 of the virus in some countries has indeed aggravated the issue of tackling the disease. The virus mainly transmits through coughs, sneezes, talks, or breathes. The air-borne transmission is also an alternate dominant route. This opinion focuses on the infection capability of SARS-CoV-2 on different surfaces and also other possible means of transmission.